Transparent self-cleaning coating of modified polydimethylsiloxane (PDMS) for real outdoor application - Syafiq, A.; Vengadaesvaran, Balakrishnan; Rahim, Nasrudin Abd; Pandey, Adarsh Kumar; Bushroa, Abdul Razak; Ramesh, Kasi; Ramesh, Subramaniam (Elsevier, 2019)
Hydrophobic coating usually possesses a water contact angle (CA) of more than 90°. The fabrication of hydrophobic coating on the glass substrate has high potential to induce self-cleaning properties, anti-fogging and mud-repellent properties. In this study, a transparent hydrophobic self-cleaning coating with modified Polydimethylsiloxane (PDMS) has been successfully developed using 3-aminopropyltriethoxyslane (APTES). APTES has a flexible amino group for silica structuration of Polydimethylsiloxane to cross-link and form a hybrid coating system. The hydrophobic coating developed is applied onto glass plates using dip-coating method. The hydrophobicity of the coating is tested using the water contact angle (WCA) method and achieved WCA as high as 103.9°. The UV-VIS spectrometer measurement reveals that the transparency of the modified APTES/ PDMS coating is above 90% in visible region. The prepared hybrid coating also exhibits excellent self-cleaning properties in indoor and outdoor environment. In addition to that, the hybrid coating also exhibits great anti-fogging behavior where the tiny water droplets on the coated surface completely disappear after 6 min at ambient temperature. © 2019 Elsevier B.V.